Quantitative Assessment of Diffusion Abnormalities in Posterior Reversible Encephalopathy Syndrome - Provenzale, James M.; Petrella, Jeffrey R.; Cruz Jr, Luiz Celso H.; Wong, Jimmie C.; Engelter, Stefan; Barboriak, Daniel P. (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: Previous studies have shown that lesions in posterior reversible encephalopathy syndrome are often isointense on diffusion-weighted MR images. We hypothesized that 1) apparent diffusion coefficient (ADC) maps using various thresholds would show larger abnormalities in posterior white matter (WM) and 2) isointense appearance of lesions on isotropic diffusion-weighted images results from a balance of T2 prolongation effects and diffusibility effects.METHODS: T2-weighted MR images from 11 patients were reviewed. Hyperintense lesions were located in both anterior and posterior WM in eight patients and solely in posterior WM in three patients. The ADC maps were produced by use of ADC values ≥ 3 SD and ≥ 10 SD above the mean value of normal WM. Lesions on diffusion-weighted images were classified as isointense or hypointense. ADC values within lesions (ADCL) were compared with those of normal WM (ADCN), and compared for isointense lesions and hypointense lesions.RESULTS: The distribution of lesions with ADC values ≥ 3 SD was essentially identical to that on T2-weighted images. Regions with ADC values ≥ 10 SD were found in both anterior WM and posterior WM in two patients and solely in posterior WM in nine patients. On diffusion-weighted images, lesions appeared isointense in seven patients and hypointense in four patients. Mean ADCL/ADCN for all lesions was 1.81; for hypointense lesions, 2.30.CONCLUSION: Vasogenic edema was more severe in posterior WM. Isointense lesions result from a balance of T2 effects and increased water diffusibility. Hypointense lesions have higher ADC values, which are not balanced by T2 effects.